Strategi Manajemen Pendidikan dalam Mengimplementasikan Moderasi Beragama di Madrasah Ibtidaiyah - Listiana, Heni (STAI YAPIS Takalar, 2025)
This research aims to identify educational management strategies for implementing religious moderation at Madrasah Ibtidaiyah (MI). Additionally, it analyzes the roles of teachers and principals in achieving this goal and offers practical solutions to existing challenges, such as a lack of understanding among teachers and socio-cultural barriers.The study used a qualitative approach with a case study method, focusing on MI Nurur Rahmah Pamekasan. Data was collected through in-depth interviews, observations, and document analysis related to the school's curriculum and policies. The findings indicate that religious moderation at MI plays a vital role in shaping moderate and inclusive student character. Although government policies support this implementation, challenges like teachers' limited understanding and socio-cultural barriers remain. The roles of teachers and principals are crucial in creating an inclusive and tolerant environment. The research suggests that strengthening managerial strategies and fostering closer synergy between schools, parents, and the community is necessary to support the implementation of religious moderation at MI.